Collective Bargaining and the Theory of Conflict - Barbash, Jack (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1979)
The purpose of this paper is to examine conflict in the bargaining context as it operates mainly in the United States, and then draw some broad inferences for the theory of conflict.